Local Economy Coinization: The Potential of Regional Cryptocurrency to Strengthen the Competitiveness of Traditional Markets - Farkhatun Zaidah (PT. Anagata Sembagi Education, 2025)
This research examines the potential implementation of regional cryptocurrency or local economic coinization as an innovative strategy to strengthen traditional market competitiveness. Through a systematic literature review of 30 recent studies, this research analyzes the opportunities, challenges, and impacts of regional crypto on transaction efficiency, financial inclusion, and economic diversification. Findings show that regional crypto can improve transparency, reduce overhead costs, and expand access to global markets. Case studies in Australia, Latin America, and Asia demonstrate that crypto adoption is driven by novelty effects, ease of adoption, and low transaction costs. However, implementation faces significant challenges including regulatory uncertainty, price volatility, lack of digital literacy, and consumer trust issues. This research finds that crypto can enhance economic competitiveness through blockchain technology innovation, increased competition, and GDP growth, but also brings risks of market manipulation, environmental impact, and economic instability. The research conclusion emphasizes that the success of local economic coinization depends heavily on adaptive regulation, improved digital literacy, and readiness of local technology ecosystems.